Genesis of High-Mg Adakites in the Southeastern Margin of North China Craton: Geochemical and U-Pb Geochronological Perspectives - Zheng, Shuo; An, Yanfei; Lai, Chunkit; Wang, Hongzhi; Li, Yunfeng (Frontiers in Earth Science, 2021)
In the eastern North China Craton (NCC), Mesozoic tectonics was dominated by the Paleo-Pacific subduction rollback and the Tanlu crustal-scale fault movement. The regional transtension had generated extensive adakitic magmatism, some Cu-Au ore-forming but others not. To establish the geodynamic setting and any metallogenic link for the adakites from the southeastern NCC margin, we analyzed the ore-barren adakitic rocks from underground mines in the Huaibei-Linhuan coalfield (where surface igneous outcrops are scarce), and compared their ages and geochemistry with other mineralized and ore-barren adakites across Eastern China. Zircon U-Pb dating reveals two magmatic episodes in the Huaibei-Linhuan coalfield: (1) early-Early Cretaceous (ca. 130–129 Ma) (quartz-)diorite and granodiorite, and (2) late-Early Cretaceous (ca. 115.8 and 105.8 Ma) microgabbro and dolerite. Whole-rock geochemistry indicates that the (quartz-)diorite and granodiorite are high-Mg adakitic, featured by low K2O/Na2O (avg. 0.33), high Sr/La (avg. 44.3), and lack of correlation between SiO2 (fractionation index) and Sr/Y (avg. 56.55) and MREE/HREE (avg. 1.09), resembling typical adakites derived from oceanic-slab partial melting. Geochronological correlation with the regional tectonic events suggests that the slab-melting may have been caused by the Paleo-Pacific subduction rollback. Further extension and crustal thinning in the late-Early Cretaceous along the southern Tanlu fault may have formed the gabbro-dolerite in the coalfield. Geochemical comparison suggests that parental magma of the Huaibei-Linhuan adakites may have had similar water content (similar zircon 10,000*(Eu/Eu*)/Y and Eu/Eu* ratios) to typical porphyry Cu-Au ore-forming magmas, yet the former may have been considerably more reduced (lower zircon Ce/Nd and whole-rock V/Sc ratios). We considered that the assimilation of Carboniferous-Permian coal seams in the area may have further lowered the magma fO2 and thus its potential to form Cu-Au mineralization.